Video Modeling for Children with Dual Diagnosis of Deafness or Hard of Hearing and Autism Spectrum Disorder to Promote Peer Interaction - Thrasher, Amy (Seminars in Speech and Language, 2014)
This article describes an intervention program offered at the University of Colorado Boulder that supports peer interaction among young children with autism spectrum disorders and their typical peers using a multicomponent approach, including video modeling. Characteristics of autism that may interfere with the development of peer interaction in young children will be discussed. Components of the approach will be described and the evidence base for the application of these components examined in regards to children with autism and for the potential application to children with the dual diagnosis of autism and deafness or hard of hearing.
Keywords: Autism; deaf; intervention; video modeling; peer interaction